2009
DOI: 10.1007/s00417-009-1133-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible factor−1α and −2α in human choroidal neovascular membranes

Abstract: The localization of HIF expression supports the concept that hypoxia is a major stimulus for the development of submacular wound healing and within this context CNV is but one component of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 27 publications
0
58
2
Order By: Relevance
“…This may lead to reduced oxygen tension causing the activation of a hypoxic response, which may lead to the development of neovascular complications. In this response, HIF factors may again be the driving force controlling initiation and progression of the devastating vessel growth (Inoue et al, 2007;Sheridan et al, 2009). The main pro-angiogenic factor in wet AMD seems to be VEGF.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…This may lead to reduced oxygen tension causing the activation of a hypoxic response, which may lead to the development of neovascular complications. In this response, HIF factors may again be the driving force controlling initiation and progression of the devastating vessel growth (Inoue et al, 2007;Sheridan et al, 2009). The main pro-angiogenic factor in wet AMD seems to be VEGF.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Retinal pigment epithelial (RPE) cells, located between the neurosensory retina and the vascular choroids, form the outer blood retinal barrier and have an important role in the pathogenesis of CNV (2). Hypoxia is also essential for the pathogenesis of CNV (3). Increasing research suggests that vascular endothelial growth factor (VEGF) upregulation produced by RPE cells under hypoxic conditions is a major angiogenic factor for CNV (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has also been shown that CNV membranes are positive for HIF-1 expression, and this expression tends to be localized to the retinal pigment epithelium (RPE) cells. 23, 24 As a 'master switch' for mammalian circulation in response to low oxygen tension, HIF-1 regulates the transcription of many proangiogenic growth factors, including VEGF, erythropoietin and platelet-derived growth factor. 25,26 Knocking down of HIF-1a gene results in the down regulation of VEGF.…”
Section: Introductionmentioning
confidence: 99%